1988
DOI: 10.1021/jm00117a028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro activity of various derivatives of a novel thromboxane receptor antagonist, (.+-.)-(5Z)-7-[3-endo[(phenylsulfonyl)amino]bicyclo[2.2.1]hept-2-exo-yl]heptenoic acid

Abstract: Several sulfonyl derivatives (13a-t) of (+/-)-(5Z)-7-(3-endo-aminobicyclo[2.2.1]hept-2-exo-yl)heptenoic acid (VI) were synthesized via its methyl ester 10. Sulfonylation of 10 with 11a-t followed by saponification yielded 13a-t. Inhibitory concentrations (IC50) of the corresponding sodium salts 14a-t for platelet aggregation were measured with rat washed platelets (WP) and rabbit platelet-rich plasma (PRP). IC50 values of some derivatives for contraction of the rat aorta were also measured. The IC50 values for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
3

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(15 citation statements)
references
References 0 publications
0
12
0
3
Order By: Relevance
“…The biological effects of TxA 2 are mediated by the cell‐surface TxA 2 receptor (TP‐receptor) (Coleman et al , 1989), the cDNA of which has been cloned for man (Hirata et al , 1991), rats (Abe et al , 1995) and mice (Namba et al , 1992). Therefore, much effort has been directed towards the development of selective TP‐receptor antagonists (Lefer & Darius, 1987; Narisada et al , 1988; Ohtani et al , 1991), and the antagonists have been reported to be effective in a variety of experimental models including coronary thrombosis, cerebral vasospasm, ischaemia and reperfusion arrhythmias, and allergic asthma (Coleman et al , 1989; Mihara et al , 1989; Nakajima & Ueda, 1989; Arimura et al , 1992; 1994a, b; Matsuo et al , 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The biological effects of TxA 2 are mediated by the cell‐surface TxA 2 receptor (TP‐receptor) (Coleman et al , 1989), the cDNA of which has been cloned for man (Hirata et al , 1991), rats (Abe et al , 1995) and mice (Namba et al , 1992). Therefore, much effort has been directed towards the development of selective TP‐receptor antagonists (Lefer & Darius, 1987; Narisada et al , 1988; Ohtani et al , 1991), and the antagonists have been reported to be effective in a variety of experimental models including coronary thrombosis, cerebral vasospasm, ischaemia and reperfusion arrhythmias, and allergic asthma (Coleman et al , 1989; Mihara et al , 1989; Nakajima & Ueda, 1989; Arimura et al , 1992; 1994a, b; Matsuo et al , 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In order to examine the involvement of TXA 2 in the NA‐induced EDC mediated by COX metabolites, we used a TXA 2 synthase inhibitor (OKY‐046) and a TXA 2 receptor antagonist (S‐1452) 21,22 . The TXA 2 synthase inhibitor and TXA 2 receptor antagonist did not affect NA‐induced EDC in the rat coronary artery.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that U46619 has a direct action on TXA2 in the airways. Also, S-145 is a powerful and selective TXAa/PGH 2 receptor antagonist on platelets and vascular smooth muscle [12,13,18,23]. The fact that the increase of RAR activity produced by intraatrial injections of STA2 (0.3-3.0 p~g/kg) was greatly diminished or completely blocked by administration of S-145 (0.5 mg/kg) suggests that the STA2-induced RAR stimulation occurs as a result of the activation of TXA 2 receptors in the airways and lungs.…”
Section: Discussionmentioning
confidence: 99%